Polydiacetylene a unique material to design biosensors. (2022) - Hussain, Shazidul; Deb, Rahul; Suklabaidya, Sudip; Bhattacharjee, Debajyoti; Arshad Hussain, Syed
Abstract: Polydiacetylene film has gained so much popularity because of its ability to transform from blue-to-red calorimetric transition as well as from non-fluorescent to fluorescent when it is exposed to different stimuli. Thus, PDA offers the easiest and the most convenient way for sensing where detection can be done using the naked eye. Accordingly, PDA has been already used to demonstrate various biosensors. In this review paper, the mechanism for detecting different microorganisms like bacteria, viruses, and a tool to detect diagnosing diseases like cancer, tumor, and various genetic diseases for their effective treatment also polydiacetylene sensors in the area of food technology are discussed.